Influences on Catered Event Ordering in a University Workplace: Development and Validation of the Understanding Food Ordering Survey. Issue 4 (May 2019) - Menge, Lindsey; Hu, Yueqin; Crixell, Sylvia Hurd; Lloyd, Lisa; Bezner, Janet; Burke, Tricia J
Purpose: To develop and validate an instrument to identify factors that influence what is ordered for catered events for employees at a large university. Design: Themes derived from focus groups were used to develop a survey. Setting: A large public university in central Texas. Subjects: Twenty-seven administrative assistants who order food participated in focus groups, 138 completed the survey, and 31 completed the survey a second time. Measures: One hundred fourteen-question, 5-point Likert scale survey. Analysis: Principal component analyses explored constructs. Confirmatory factor analysis confirmed structure validity. Test -retest analyses assessed reliability. Results: The final survey, the Understanding Food Ordering Survey (UFO), included 19 items within 3 factors; all factor loadings were above 0.3, with no cross-loadings. Three factors explained 55.5% of the variance. Cronbach α values of .846 for social influences from supervisors/coworkers, .838 for restrictions on ordering due to policies/vendors/attendee feedback, .893 for personal views about nutrition, and .831 for the total affirmed reliability. Test–retest reliability was acceptable ( r = 0.780), and paired samples t test indicated no differences between assessments, mean difference = −0.062, standard deviation = 0.29, t (30) = −1.18, P = .247. Structure equation modeling indicated a good fit between the proposed 3-factor model and observed data, with comparative fit index = 0.921 and root means square error of approximation = 0.074. Conclusion: Interventions to improve the nutritional quality of foods selected for catering may benefit from addressing contributory factors while considering a top-down approach to changing the workplace culture.